A cross-level study on the impact of team-based reward allocation on employees’ innovative behavior in manufacturing enterprises - LI, Tiening; Wu, Shengxia (Review of Business Management, 2024)
Purpose – This study aims to investigate the cross-level impact of different team compensation distributions on team members’ innovative work behaviors within innovative teams of Chinese manufacturing enterprises, as well as whether the task interdependence of teams has a cross-level moderating effect. Theoretical framework – Cognitive choice theory and the planned behavior theory are utilized to elucidate the relationship between team compensation distribution and team members’ innovative intentions, as well as the relationship between team members’ innovative work behaviors. Design/methodology/approach – The hypotheses are tested using cross-level structural equation modeling (MSEM) with 328 pairs of matched data from two stages and two parties across 12 manufacturing companies in China. Findings – The results show that team-based reward allocation is positively related to employee innovative behavior by promoting employee innovative intention. Task interdependence weakened the direct effect of team-based reward allocation on employee innovative intention and the indirect effect on employee innovative behavior. Research Practical & Social implications – This study reveals that the differences in team compensation distribution are one of the important factors affecting team members’ innovative behaviors. Researchers and managers should consider the degree of interdependence of the tasks undertaken by the team before implementing a certain distribution method. Originality/value – This study provides the first empirical results on how team-based reward allocation affects employee innovative behavior and examines the mechanisms and pathways of the variables involved in the context of Chinese manufacturing enterprises, contributing to filling a gap in the field of research on team compensation affecting employee innovation and expanding cross-level research on team compensation allocation.